The Role of Religiosity in Moderating the Relationship Between Gender and Tax Evasion - Ilham Illahi; Harfandi Harfandi (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
Tax evasion committed by taxpayers will reduce state revenues thereby hampering development activities. This tax evasion must be prevented so that the country's economy continues to grow and develop. This study examines the effect of gender on tax evasion. The religiosity variable is used as a moderating variable on the relationship between gender and tax evasion. This study used student respondents from the Faculty of Islamic Economics and Business (FEBI) IAIN Bukittinggi. The use of FEBI IAIN Bukittinggi students in this research is because they will later join the business world as either owners or workers and at that time they will automatically have an obligation to pay taxes. To see the effect of the gender variable on tax evasion and the moderating effect of the religiosity variable, the researcher used Moderated Regression Analysis (MRA. The results of this study found that (1) gender did not have a negative impact on tax evasion, (2) the religiosity variable was proven to moderate the relationship between gender and tax evasion. Gender with a high level of religiosity tends to avoid tax evasion because tax evasion is contrary to religious values.